Exploration of Folk Games in MTs Students' Procedural Text Writing Learning Through the PPJBL Model - Mulya, Okta Hari; Faizah, Hasnah; Charlina, Charlina (FKIP - Universitas Riau, 2025)
This study aims to explore the use of folk games as a learning medium in writing procedural texts at the Madrasah Tsanawiyah (MTS) level through the application of the Project-Based and Problem-Based Learning (PPJBL) model. Folk games were chosen because they have the potential to increase students' motivation, participation, and understanding of the material being taught. This study uses a qualitative method with a descriptive approach. Data collection was carried out through observation, in-depth interviews, and document analysis involving students and teachers as participants. Data analysis was carried out using thematic analysis techniques to identify patterns of student understanding in writing procedural texts after participating in folk game-based learning. The results of the study showed that the integration of folk games through the PPJBL model was able to increase students' creativity and collaboration, as well as provide a deeper understanding of the structure and steps in writing procedural texts. In addition, students showed more active and enthusiastic involvement during the learning process. Based on these findings, folk games can be used as an alternative effective learning medium for teaching writing skills, especially in writing procedural texts.